(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This study uses Uzbekistan as a case study to investigate the stages of development and present level of e-government in post-Soviet transition countries. The prior research on e-government in developing nations underlined the system’s significant benefits, such as improved state service delivery, reduced corruption, and more open and inclusive governance. According to the study, post-Soviet countries in transition have a variety of obstacles that keep them from realizing the benefits of digital transformation in the public sector.